Lithium nephropathy: Unique sonographic appearance and application of new on cart tools. Issue 1 (12th February 2020) - Kapkanova, Natasha; Elliott, Carla; Lucas, Deneah
Abstract: Renal toxicity is a well‐known side effect of long‐term lithium use, which may lead to chronic renal failure. Ultrasonography is effective in the assessment of this unique disorder. This case report describes the ultrasound appearances of lithium nephropathy in a 65‐year‐old female on long‐term lithium use. It will also discuss the application of shear wave elastography (SWE), the use of the hepatorenal index (HRI), and MicroPure as potential aids in the diagnosis of this condition.